Dicranomyia crane flies (Diptera: Limoniidae) of Korea - Podenas, Sigitas; Seo, Hong Yul; Kim, Taewoo; Hur, Jun Mi; Kim, A Young; Klein, Terry A.; Kim, Heung Chul; Kang, Tae Hwa; Aukštikalnienė, Rasa (Zootaxa, 2019)
A total of 38 Korean species of crane flies belonging to the genus Dicranomyia Stephens, 1829 (Diptera: Limoniidae: Limoniinae) are taxonomically revised. No species of Dicranomyia were previously reported from South Korea, and only twelve species were reported from North Korea. New records of Dicranomyia from the Korean Peninsula include: D. (Dicranomyia) depauperata Alexander, 1918, D. (D.) distendens pallida Savchenko, 1983, D. (D.) handlirschi handlirschi Lackschewitz, 1928, D. (D.) hyalinata (Zetterstedt, 1851), D. (D.) kandybinae Savchenko, 1987, D. (D.) longipennis (Schummel, 1829), D. (D.) mesosternatoides Alexander, 1924, D. (D.) modesta (Meigen, 1818), D. (D.) pammelas Alexander, 1925, D. (D.) poli (Alexander, 1941), D. (D.) sera (Walker, 1848), D. (D.) shinanoensis (Alexander, 1933), D. (D.) takeuchii Alexander, 1922, D. (D.) unispinosa Alexander, 1921, D. (Erostrata) globithorax Osten Sacken, 1869, D. (E.) globulithorax Alexander, 1924, D. (E.) yazuensis Kato et al., 2018, D. (Glochina) basifusca Alexander, 1919, D. (Melanolimonia) paramorio platysoma (Alexander, 1933), D. (Numantia) fusca (Meigen, 1804), D. (Sivalimnobia) euphileta (Alexander, 1924). Species D. (D.) byuni Podenas, sp. nov., D. (D.) cornuta Podenas, sp. nov., D. (D.) jirisana Podenas, sp. nov., D. (D.) petrasiuni Podenas, sp. nov., and D. (D.) yankovskyi Podenas, sp. nov. are described. An additional ten new records are reported from North Korea, bringing the total number of Dicranomyia species known from North Korea to 22 species. South Korea has a greater diversity of Dicranomyia with total number of 30 species. D. (D.) amurensis Alexander, 1925 is synonymised with D. (D.) hyalinata (Zetterstedt, 1851). An illustrated key with redescriptions and photographs of all species and both sexes of adults collected in Korea are presented. Most females are illustrated or described for the first time. Elevation range, period of activity, habitat information, general distribution and a distribution map in Korean Peninsula is given for each species.